Myth, Memory, and Market: Exploring Cultural Mythology in ‎Consumer Brand Perceptions - Anute, Dr. Nilesh; Tripathi , Dr. Mayank; Chawla , Dr. Namita; Havale, Dr. Dhanashri S.; Kalshetti , Dr. Prashant; Pathak , Dr. Ganesh; Tripathi, Dr. Shailesh (International Journal of Accounting and Economics Studies, 2025)
In a competitive marketplace, consumer perceptions of brands encompass not only ‎functionality and quality but also important cultural narratives and mythologies. ‎This research examines the relationship among cultural mythology, collective ‎memory, and branding, highlighting the impact of traditional myths and symbolic ‎associations on consumer choices, loyalty, and perceptions of brand authenticity. ‎This study analyzes the utilization of mythological characteristics, including ‎archetypes, heroes, rituals, and nostalgia, by brands to shape consumer perceptions ‎and enhance market resonance, based on cultural semiotics and consumer ‎psychology.‎A standardized questionnaire was distributed to a sample of 180 respondents from ‎urban and semi-urban areas, encompassing various age groups, genders, and ‎educational backgrounds. A quantitative analysis was performed on demographic ‎data and responses to 21 closed-ended questions to identify trends and correlations ‎associated with mythology-infused branding. The findings indicate that consumers ‎unconsciously associate brand narratives with cultural myths, and brands that align ‎with established mythic frameworks generally improve emotional attachment and ‎brand recall.‎Generational memory and regional culture significantly influence brand ‎perceptions, indicating that effective branding strategies must incorporate cultural ‎context. This study contributes to marketing literature by clarifying the role of ‎symbolic communication and cultural storytelling in promoting consumer ‎engagement and preference‎.
Keywords: Brand Mythology; Cultural Narrative; Consumer Perception; Archetypes; Brand ‎Symbolism; Memory Marketing; Emotional Branding; Cultural Identity.